The lymph node ratio does not provide additional prognostic information compared with the N1/N2 classification in Stage III colon cancer. (February 2017) - Mohan, H. M.; Walsh, C.; Kennelly, R.; Ng, C. H.; O'Connell, P. R.; Hyland, J. M.; Hanly, A.; Martin, S.; Gibbons, D.; Sheahan, K.; Winter, D. C.
Abstract: Aim: The ratio of positive nodes to total nodes, the lymph node ratio (LNR), is a proposed alternative to the current N1/N2 classification of nodal disease. The true clinical benefit of adopting the LNR, however, has not been definitively demonstrated. This study compared the LNR with the current N1/N2 classification of Stage III colon cancer. Method: Patients with Stage III colon cancer were identified from a prospectively maintained database (1996–2012). The specificity and sensitivity of the N1/N2 classification in the prediction of overall survival were determined using R. A cut‐off point for the LNR was determined by setting the specificity the same as for the N1/N2 classification. The sensitivity of the two methods was then compared, and bootstrapping 1000‐fold was performed. This was then repeated for disease‐specific survival. Results: The specificity and sensitivity of the N1/N2 classification in predicting 3‐year overall survival in this cohort ( n = 402) was 62.2% and 52.1%, respectively. The cut‐off point for the LNR was determined to be 0.27 for these data. On comparing LNR with the N1/N2 classification showed that for a given specificity, the LNR did not provide a statistically significant improvement in sensitivity (52.8% vs 52.1%, P = 0.31). For disease‐specific death at 3 years, the specificity and sensitivity were 60.8% and 54.6%, respectively. The LNR did not provide a statistically significant improvement (55.4% vs 54.6%, P = 0.44). Conclusion: Both the N1/N2 system and the LNR predict survival in colon cancer, but both have low specificity and sensitivity. The LNR does not provide additional prognostic value to current staging for overall or disease‐specific survival for a given cut‐off point.